Robot Operating System: A Comprehensive Analysis and Evaluation - Patkar, U. C.; Mandhalkar, Vaishnavi; Chavan, Aayush; Songire, Shubham; Kothawade, Hrishikesh (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The Robot Operating System (ROS) has become a prominent open-source framework for the development of robot software. This research paper offers a comprehensive analysis and assessment of ROS, encompassing its fundamental features, architectural framework, ecosystem, and applications. The study delves into ROS's core elements, which include its messaging system, package management, visualization tools, and the robust support from its community. It also delves into the benefits and challenges associated with implementing ROS across diverse domains, ranging from research robotics to industrial automation and autonomous vehicles. Moreover, the paper sheds light on the future directions and emerging trends within the development of ROS. This insight equips researchers and practitioners with the knowledge to comprehend ROS's capabilities, making informed decisions when incorporating ROS into their robotic projects.